A STUDY ON THE MULTIFUNCTIONALITY OF GARDENS IN RESTAURANT INTERIORS: AESTHETICS, HEALING SPACE, AND GREEN BRANDING - Kerdiati, Ni Luh Kadek Resi; I Putu Udayana Wasista; Putu Ari Darmastuti (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2025)
This study discusses the multifunctional role of gardens in restaurant interiors through three main aspects: aesthetics, healing space, and green branding. The research focuses on the function of gardens in restaurant buildings, which are not only used as aesthetic elements, but also serve to support psychological healing and strengthen brand identity. This study employs a qualitative approach using the literature review method, by examining books, journal articles, and scientific publications relevant to the research topic. The literature selection process was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram. The findings indicate that the aesthetic, healing space, and green branding functions complement one another. From an aesthetic perspective, the presence of plants enhances the visual appearance of interior spaces. As a healing space, gardens create a relaxing atmosphere that can improve psychological comfort. In terms of green branding, gardens within restaurant buildings serve as a symbol of sustainability.This study emphasizes the integration of gardens within restaurant interiors as a strategy that combines aesthetic, psychological, and ecological values. The results provide practical insights for designers and restaurant entrepreneurs in creating interior designs that are not only visually appealing, but also function as restorative environments while remaining aligned with the principles of sustainable business.